2016
DOI: 10.1016/j.physletb.2016.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Weyl vs. conformal

Abstract: In this note we show that given a conformally invariant theory in flat space-time, it is not always possible to couple it to gravity in a Weyl invariant way.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…In this section we consider the free field theories of Refs. [21,23], which can be used to illustrate various aspects of the general arguments above. These theories are defined by the action…”
Section: Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we consider the free field theories of Refs. [21,23], which can be used to illustrate various aspects of the general arguments above. These theories are defined by the action…”
Section: Examplesmentioning
confidence: 99%
“…Ref. [23] showed that this theory is conformally invariant for all k and d in the sense that T = ∂ µ ∂ ν L µν in flat spacetime. However, for special values of d and k the theory cannot be improved to be Weyl invariant in curved spacetime: In general, the theory cannot be coupled to gravity in a Weyl invariant way for all values of k subject to the condition that d is even and d < 2k.…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation properties of the fields can be obtained from the transformation of the coset representative (18). However, the structure of the commutation relations of the Galilei group (20) is not the one presented in (17). This fact results in the mixing of the U(1) gauge field with the vielbein under boosts.…”
Section: Galilei Algebramentioning
confidence: 99%
“…In this nomenclature and related notational conventions, we have followed [30]. We should mention that some authors call this a Weyl transformation, reserving the name 'conformal transformations' for what are called 'conformal isometries' in [30] (for a discussion on the nomenclature, see [58]). This transformation alters lengths of spacetime intervals, but preserves angles.…”
Section: Introductionmentioning
confidence: 99%